Elastic modulus of a chemically bonded phosphate ceramic formulated with low-grade magnesium oxide determined by Nanoindentation. Issue 9 (November 2015) - Morales, M.; Formosa, J.; Xuriguera, E.; Niubó, M.; Segarra, M.; Chimenos, J.M.
Abstract: Statistical Nanoindentation Technique (SNT) has been applied to a Chemically Bonded Phosphate Ceramic (CBPC) formulated with Low-Grade Magnesium Oxide in order to determine its elastic modulus at micro-/nanometric scale. Mechanical and microstructural properties for the CBPC phases were correlated by combining the SNT and the scanning Electron Microscope equipped with Energy Dispersive X-ray analysis (SEM-EDX). The elastic modulus of the main aggregate (periclase) was significantly higher than that of the K-struvite matrix, thus enhancing the overall mechanical response of CBPC. Interface Transition Zone between the periclase and the K-struvite was also characterized by Nanoindentation and SEM-EDX analysis, which corroborated their appropriated mechanical interaction. Finally, the elastic modulus of CBPC was determined by resonance frequency technique. The correlation of this mechanical property at both micro- and macroscopic scales was found to be independently of the porosity involved at the macroscopic scale for different studied samples, thus confirming the results obtained by SNT.